Was kann/soll bei Nierentumoren wann behandelt werden - Sommer, Christof-Matthias; Vollherbst, Dominik; Kauczor, Hans-Ulrich (Der Radiologe, 2017)
Clinical/methodical issue: In the treatment of localized renal cell carcinoma, the lack of randomization in controlled trials on thermal ablation is a major limitation. The latter leads to significant study bias and it ultimately remains unclear whether the improved overall survival in favor of partial nephrectomy can actually be attributed to the treatment method. Standard radiological methods: For T1a (≤4 cm) renal cell carcinoma without lymph node and distant metastases, excellent technical and clinical results have been described after imaging-guided radiofrequency ablation and cryoablation. Methodical innovations: Low major complication rates, preservation of renal function and three-dimensional confirmation of negative ablation margins (A0 ablation) are the advantages of computed tomography (CT)-guided thermal ablation. Performance: According to the results of controlled (non-randomized) trials on T1a renal cell cancer, the cancer-specific survival rates are comparable between ablative and surgical techniques.AchievementsIt is high time for prospective randomized controlled trials to define the actual value of percutaneous thermal ablation and partial nephrectomy in the treatment of T1a renal cell carcinoma.Practical recommendations: Apart from localized renal cell carcinoma, angiomyolipoma and oncocytoma can be treated by thermal ablation. Transarterial embolization extends the radiological spectrum for the treatment of renal tumors, either as complementary embolization (e. g. before thermal ablation of T1a and T1b renal cell carcinoma), prophylactic embolization (e. g. angiomyolipoma >6 cm), preoperative embolization (e. g. before laparoscopic partial nephrectomy) or palliative embolization (e. g. in patients with symptomatic macrohematuria due to renal cell carcinoma)